Icons : Magnets of meaning - Betsky, Aaron; Flusty, Steven; Lane, John R.; Nye, David E.; Pearlman, Chee (San Francisco : San Francisco Museum of Modern Art, 1997)
Moulton, Peggy ; Beuys, Joseph ; Braun, Craig ; Warhol, Andy ; McNatton, Gary ; Noguchi, Isamu ; Hillerich & Bradsby ; Egger, Robert ; Yagi, Tamotsu ; Starck, Philippe ; McCoy, Michael ; Gehry, Frank ; Alessi ; Chan, Eric ; Dyson, James ; Davidson, Carolyn ; Friedman, Dan ; Disney, Walt ; Bonauro, Tom ; Vanderlans, Rudy ; Swanlund, Gail ; Adigard, Erik ; Sciullo, Pierre Di ; Wessel, Henry ; Saee, Michele ; Bridges, Marilyn ; Predock, Antoine ; Gehry, Frank ; Ruscha, Ed ; Simpson, Veldon ; Predock, Antoine ; Bruder, William P. ; Rigolini, Luciano ; McAuley, Skeet ; Denari, Neil ; Sachs, Tom ; Stirling, James ; Wilford, Michael ; Rubio, Cesar ; Jones, Pfau ; Hinshaw, Holt ; Botta, Mario ; Lefebvre, Regis ; Le Corbusier
Icons : Magnets of meaning, San Francisco Museum of Modern Art, San Francisco, April 18 to August 5, 1997
Engels
boek